Cancer therapy: know your enemy? - Westhoff, Mike-Andrew (Mol Cell Pediatr, 2014)
BACKGROUND: Most cancer therapies are devised for adult or even elder patients. However, when dealing with pediatric cancers, additional considerations are needed. CONCLUSIONS: This review discusses non-classic components of tumors and highlights possible treatment approaches which might be of particular benefit for children and adolescents.